Elucidating the hydrogen-entry-obstruction mechanism of a newly developed aluminum-based coating in high-pressure gaseous hydrogen. (24th August 2015) - Yamabe, Junichiro; Awane, Tohru; Matsuoka, Saburo
Abstract This study presents a precise hydrogen-barrier mechanism of a newly developed three-layer (alumina/aluminum/ferro-aluminum) aluminum-based coating in high-pressure gaseous hydrogen. After exposure to high-pressure gaseous hydrogen, the hydrogen content of the specimen with a palladium-sputtered aluminum-based coating was the same as that of the specimen with aluminum-based coating, but without palladium. Furthermore, the hydrogen content of the coated specimens increased with a decrease in the specimen size. These results indicate that the hydrogen entered by a diffusion-controlled process. The effective diffusivity of the coated specimen was approximately one thousandth of that of base steel (type 304 stainless). Such excellent resistance could not be obtained with a two-layer coating (alumina/ferro-aluminum). Analysis of local hydrogen concentrations by secondary ion mass spectroscopy demonstrated that the extremely low effective hydrogen diffusivity of the three-layer-coated specimen was attributed to hydrogen trapping at the aluminum–ferro-aluminum interface, and not to the hydrogen-entry obstruction by the aluminum layer.